Studi Eksperimen Pada Unit Kegiatan Mahasiswa Petanque Universitas Islam Riau: Meningkatkan Kesegaran Jasmani Melalui Permainan Hadang dan Bentengan - Apriani, Leni; Sari, Merlina; Alpen, Joni (Jurnal MensSana, 2021)
The purpose of this study was to determine and test the increase in physical fitness through bentengan and obstacle course games. In this study the authors used an experimental method. From the results of paired samples test, it can be seen that the significance value is 0.038, which is smaller than α = 0.05. These results prove that using the game hadang has a significant effect on increasing the level of physical fitness of UIR Petanque UKM athletes. A different thing happened to the fortress game that it was not significantly proven to the level of physical fitness of the Petanque UIR UKM athletes with a value of 0.603. If seen in table 1 the mean value of the game hadang was 1.12, while the game of bentengan was -62, this could mean that the game hadang better than the clash of arms.